Books, bluster, and bounty: local politics in the Intermountain West and Carnegie library building grants, 1898-1920 - Swetnam, Susan H., author; Utah State University Press, publisher (Colorado State University. Libraries, 2012)
Susan Swetnam uses case studies of western applications for Carnegie libraries to examine how local support was mustered for cultural institutions in the late nineteenth and early twentieth century interior West. This is a comparative study involving the entire region between the Rockies and the Cascades/Sierras, including all of Idaho, Utah, Nevada, and Arizona, western Montana, Wyoming, and Colorado, eastern Oregon and Washington and small parts of California and New Mexico. The study addresses not just the how of the process of establishing Carnegie libraries but, more importantly, the variable why. Although virtually all citizens and communities in the West who sought Carnegie libraries were after tangible benefits that were only tangentially related to books, what they specifically wanted varied in correlation with the diversity of the communities of the West: Library proponents in Inland Empire boom towns, for example, touted Carnegie libraries to their fellow citizens as instruments of economic advantage over rival communities citizens in rural LDS communities promoted Carnegie libraries as a force against the encroaching secular influences they feared threatened their children a small cadre of Carnegie library proponents in several of Utah's largest cities, in stark contrast, actually promoted the projects to their fellow Gentiles as a corrective to LDS insularity. Economically stable Idaho communities sought Carnegie libraries to reinforce their self-perceived cultural superiority communities in newly American Arizona sought them to counter perceptions of their towns as 'Hispanic mud villages.' And so on'.--Provided by publisher.
Keywords: Carnegie libraries -- West (U.S.) -- History